Quantifying the injury of the human eye components due to tennis ball impact using a computational fluid–structure interaction model. Issue 2 (June 2016) - Karimi, Alireza; Razaghi, Reza; Navidbakhsh, Mahdi; Sera, Toshihiro; Kudo, Susumu
Abstract Although it might be believed that the eye only comprised a very small area of the face, its injury due to the ball impacts in different sports seems to be severe enough to entice many researchers to determine the level of injury and then attempt to minimize it. Sports-related eye injuries, especially tennis, pose a substantial and preventable problem to the eye due to the high speed of the tennis ball (69 m/s). This is why many ophthalmologists provide a wide range of information for their patients regarding the risks of eye injuries in tennis to prevent the injury to well over 100, 000 eyes each year. However, so far although there are some general information regarding the injury to the human eye components due to the tennis ball impact, the details of the stresses and deformations have not been well determined. Therefore, the goal of this study was to determine the stresses and deformations of the eye components, including cornea, aqueous body, iris, ciliary body, lens, vitreous body, retina, sclera, optic nerve, extra and intraconal fats, and muscles, attributable to the tennis ball impact via a Lagrangian–Eulerian computational coupling model. Magnetic resonance imaging was employed to establish a finite element model of the human eye according to a normal human eye. The numerical results revealed the highest amount of stress in the iris (19.2 MPa), whereas the lowest one was observed in the vitreous body (1.77 Pa). The cornea also experienced the stress of 8.27 MPa which might be high enough to invoke rupture in this delicate material. In addition, the results exhibited a decreasing and increasing of the radius of curvature for the cornea and lens, respectively. Finally, the collision of the tennis ball to the eye triggered the resultant displacement of 0.045 µm in the optic nerve which may imply a non-significant injury to that. The findings of this study may have implications not only for understating the values of stresses and deformations in the human eye components but also for helping the ophthalmologists to have a more precise diagnosis about the injury position in the eye due to the tennis ball impact.